Upaya Peningakatan Lahan Kosong Eko Wisata Waduk Tanjungan di Kecamatan Kemlagi - Hascaria Budi Prasetiyo; Abdul Rokhim; Adelya Rizki Asmedianti; Arif Wibisono; Arinda Bagus Wicaksono; Bayu Timur Aji; Dimas Khoirul Habib; Faisal Isflah Huda; Frella Dwi Rusanda; Geulis Enes Wahyuning Tiyas; Irsya‘Adah; Khoirum Maulana Ishaq; Lailatul Nabilah Indah Cahyani; Lelly Kusirawati; Lifta Kaumala Febriyanti; Muhammad Afrizal Firmansah; Muhammad Endy Harjono; Regita Cahyani Salsabilla; Renaldi Dwi Setiawan; Syaiful Fuadi; Sylvi Amalia Annisa; Tatik Tatik; Thesa Adelia Kusuma; Vino Julys Pramudito; Yulia Frasetia Ningsih (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Tanjungan Village is a tourist village that has large potential land for farming. The problem that exists in this village is that land use is less than optimal for activities such as farming, so it is necessary to provide assistance to the community which aims to increase land use more effectively than before for planting various vegetable crops by the people of Tanjungan Village.